Corporate Social Responsibility [CSR] Initiatives of Companies in India - Ramakrishnan, M. K.; Reshma, K. P. (Prabandhan: Indian Journal of Management, 2010)
The present day businesses continuously innovate by introducing drastic changes in priorities and bringing consensus on critical success factors. Several such factors that had been put in the backburner by yesterday’s managers were pushed to the limelight by today’s businesses for survival and growth. The issue of stakeholder welfare is one of such factors that received greater attention from management all over the world. This has contributed wide spread thinking about humanizing and democratizing the process of administration. One of the aspects that is thought of and refined more in the present context on stakeholder welfare is the concept of Corporate Social Responsibility [CSR]. Every business organization is working out a model to implement their CSR initiatives according to the vision of their respective organization.